Administrative Supervision of Lesson Planning, Learning Activities, and Assessment in an Elementary School Setting - Putri Anggreini, Nadia; Hanif, Ma'mun (Universitas Islam negeri Mahmud Yunus Batusangkar, 2023)
This study aims to elucidate educational supervision related to learning assessment at Elementary School. A qualitative descriptive approach was utilized through observation and interviews. The research results provide feedback for the school principal and teachers at SD Negeri Salit Kajen, enhancing readers' understanding. Supervision of administrative lesson planning, instructional activities, and learning assessment is deemed effective. The school principal conducts supervision annually, involving the preparation of documents such as Annual Programs, Semester Programs, ATP, Teaching Modules, Academic Calendars, and others. Data analysis indicates that instructional supervision occurs directly in classrooms, and assessment supervision aims to enhance educational quality by encouraging teachers' self-evaluation annually.┬á┬á┬á